The Development of Management Theory in Business Organizations, an Overview of the Science Philosophy Perspective - Miswaanto Miswanto (Politeknik Negeri Bengkalis, 2020)
Based on the philosophy of science, the development of management science uses the perspective of ontology, epistemology, and axiology. In the perspective of ontology, the essence of management theory in business organizations is the science that offers a management process so that business organizations can achieve their goals. The final goal to be achieved by the process this management is the achievement or fulfillment of goals that have been set. Based on an epistemological perspective, management theory in business organizations introduces methods or ways of making decisions or solving problems that can be used by managers in running business organizations. In addition, management science introduces various management theories to be practiced in business activities. In an axiological perspective, ethical values and social responsibility must be a serious concern in applying management science to business organizations. In management theory, business orientation is not only looking for profit but also give attention to the norms prevailing in society and give attention to the interests and welfare of all parties. Because management theory has the perspective of ontology, epistemology, and axiology, management theory is really a philosophy of science. Therefore, management theory needs to be developed to be implemented in business organizations.